Repair of syndesmosis injury in ankle fractures: Current state of the art. Issue 1 (25th January 2018) - Mak, May Fong; Stern, Richard; Assal, Mathieu
Abstract : Conventional treatment of syndesmosis injuries in rotationally unstable ankle fractures is associated with an unacceptably high rate of malreduction, and this has led to a paradigm shift in the approach to a newer concept of anatomical repair. In the anatomical approach, the principle is to 'directly fix what is broken and repair what is torn'. The approach is effective in reducing the rate of syndesmosis malreduction, increasing the biomechanical strength of syndesmosis fixation and avoiding the need for trans-syndesmotic fixation and its secondary removal. The objective of this review article is to compare the conventional treatment of these injuries (accepted usage, general consent, traditional, generally accepted) with a newer anatomical approach to be considered as a shift in thinking. Cite this article: EFORT Open Rev 2018;3:24-29. DOI: 10.1302/2058-5241.3.170017